Impact of duration of untreated psychosis in short‐term response to treatment and outcome in antipsychotic naïve first‐episode psychosis. Issue 6 (21st October 2019) - Cavalcante, Daniel A.; Coutinho, Luccas S.; Ortiz, Bruno B.; Noto, Mariane N.; Cordeiro, Quirino; Ota, Vanessa K.; Belangeiro, Sintia I.; Bressan, Rodrigo A.; Gadelha, Ary; Noto, Cristiano
Abstract: Aim: Duration of untreated psychosis (DUP) is one of the few potentially modifiable outcome predictors in psychosis. Previous studies have associated a longer DUP with a poor prognosis, but few of them were performed in countries with low and middle level of income. This study aimed to investigate the DUP in a Brazilian sample of antipsychotic‐naïve first‐episode psychosis (AN‐FEP) patients and its association with clinical characteristics and treatment outcomes in a short‐term follow‐up. Methods: One hundred forty‐five AN‐FEP patients between 16 and 40 years were enrolled and were reassessed 10 weeks after risperidone treatment. We investigated the association between DUP and symptom severity, functionality and response to treatment, using the Positive and Negative Syndrome Scale (PANSS), the Clinical Global Impression—Severity Scale (CGI) and the Global Assessment of Functionality (GAF) scale. DUP was defined as the period between the onset of the first psychotic symptoms and the first effective antipsychotic treatment. For the analysis, we performed multivariate linear regressions. Results: The DUP's median was 61 days. At baseline, we did not find any significant association between DUP and clinical characteristics. After treatment, the longer DUP predicted worse positive and negative symptom dimensions, worse total PANSS, GAF and CGI scores and poorer response to treatment. Conclusion: Our results showed that DUP is associated with worse outcomes after short treatment, but it does not modify the baseline clinical profile of the AN‐FEP patients. Such results reinforce the need to develop early intervention strategies, reducing DUP.